(untitled) (Journal of Medicine, 2024)
Introduction: Dengue is a significant public health concern for Bangladesh with recurrent epidemics. This study aimed to investigate the clinical and biochemical presentations and identify risk factors for severe dengue among patients admitted to a tertiary care hospital during the 2023 epidemic in Bangladesh. Methods: This cross-sectional study was conducted at a tertiary care hospital in Bangladesh between July and September 2023. Data were collected from 176 adult patients with serologically confirmed dengue infection. Clinical and laboratory parameters were recorded, and severity of dengue was categorized according to WHO guidelines. Logistic regression was performed to identify predictors of severe dengue. Results: Of the 176 patients included, 113 had severe dengue and 63 had non-severe dengue. The mean age was 34.5 (SD 14.3) years, with a male-female ratio of 1:1.07. Conventional symptoms including fever, myalgia, headache, and retro-orbital pain were present in majority of patients, with warning signs present in twothirds of them. Laboratory findings showed leukocytopenia (53%), thrombocytopenia (25.6%), elevated hematocrit level (4.5%), elevated ALT, AST and ferritin level (36%, 24% and 50% respectively). Logistic regression identified persistent vomiting (aOR 3.22, 95% CI 1.41–8.04), clinical fluid accumulation (aOR 2.23, 95% CI 1.13–5.74), and elevated serum AST (aOR 3.13, 95% CI 1.30–7.79) as predictors of severe dengue. Conclusion: Most dengue cases presented with typical symptoms and warning signs, with associated laboratory abnormalities. Persistent vomiting, clinical fluid accumulation, and elevated serum AST levels upon admission could predict severe dengue. J MEDICINE 2024; 25: 121-128